2005
DOI: 10.2174/1573399052952604
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Posttransplantation Diabetes Mellitus: Insulin Resistance or Insulinopenia? Impact of Immunosuppressive Drugs, Cytomegalovirus and Hepatitis C Virus Infection

Abstract: New-onset PTDM is characterized by a variety of clinical manifestations, ranging from predominantly insulin resistance which can be handled with lifestyle intervention, to beta-cell failure requiring insulin treatment. The etiology is multi-factorial, but diabetogenic immunosuppressive drugs are of major importance. Future studies should therefore address the effects of different immunosuppressive regimens on the incidence of PTDM. In addition, the impact of cytomegalovirus infection and hepatitis C on PTDM ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 104 publications
(157 reference statements)
1
50
0
Order By: Relevance
“…8 It has long been known that CsA treatment is correlated with the onset of PTDM, for reasons that remain to be elucidated. 3,29,30 The differing effects of two ZnT-8 variants on GSIS suggest that patients undergoing CsA immunosuppressive treatment who have the 'low-risk' ZnT-8 variant (W325) may retain insulin-secreting capacity compared with those who have the 'high-risk' variant; this may account for the protective ZnT-8 polymorphism and cyclosporin A I Kim et al effect of the W325 allele with respect to PTDM. This also suggests that impairment of insulin secretion by CsA may contribute to PTDM.…”
Section: Discussionmentioning
confidence: 99%
“…8 It has long been known that CsA treatment is correlated with the onset of PTDM, for reasons that remain to be elucidated. 3,29,30 The differing effects of two ZnT-8 variants on GSIS suggest that patients undergoing CsA immunosuppressive treatment who have the 'low-risk' ZnT-8 variant (W325) may retain insulin-secreting capacity compared with those who have the 'high-risk' variant; this may account for the protective ZnT-8 polymorphism and cyclosporin A I Kim et al effect of the W325 allele with respect to PTDM. This also suggests that impairment of insulin secretion by CsA may contribute to PTDM.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance and relative insulin deficiency are involved in the pathogenesis of both disorders [93]. The impact of insulin deficiency and insulin resistance may vary in the presence of different risk factors; among these, the type of immunosuppressant accounted for 74% of the variability in the 12-month cumulative incidence of NODAT [94].…”
Section: New-onset Diabetes Mellitus After Solid Organ Transplantationmentioning
confidence: 99%
“…The predominant underlying mechanism is increased insulin resistance based on OGTTtest (OGTT) [93]. In vivo and in vitro animal studies have demonstrated that GC interfere at several steps in the insulin signaling cascade in skeletal muscles, resulting in reduced glucose uptake and glycogen synthesis [98].…”
Section: Glucocorticoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[100] Cytomegalovirus infection increases the activity of tumor necrosis factor(TNF), TNF can affect the function of islet B cell and decrease the organism's sensitivity to insulin, that will promote insulin resistance in renal transplant recipients.…”
Section: Virus Infectionmentioning
confidence: 99%